RNA Extraction from Animal and Human's Cancerous Tissues: Does Tissue Matter? - Samadani, Ali Akbar (Int J Mol Cell Med, 2015)
The reliability of gene expression profiling, based technologies and methods to find transcriptional differences representative of the original samples is influenced by the quality of the extracted RNA. Hence, RNA extraction is the first step to investigate the gene expression and its function. Consequently, the quality of extracted RNA is really significant. Correspondingly, this research was accomplished to optimize the RNA extraction methods and compare the amounts of tissue or quality of tissue. Relatively, the cancerous tissue of human stomach in fresh and frozen conditions and also the mouse fresh tissue were studied. Some factors like the amount of samples, efficacy differences of diverse extraction buffers (TriPure, Trizol) and also the efficacy of b-mercaptoethanol were compared and investigated. The results indicated that the less amount (1-2 mg) compared to other amounts (2-5 mg, 5-15 mg) yielded the best quality and the RNA bands (5S, 18S, 28S) were observed perfectly. Relatively, comparing and measuring some kinds of buffers (Trizol, TriPure) indicated no difference in RNA extraction quality. The last investigated factor was the effect of b- mercaptoethanol which was used along with TriPure to remove the RNAse. Conclusively, no effective impression was observed.